Factors Influencing Consumers' Online Shopping Behaviour: A Study of Shopee in Malaysia - Wong, Yi Hui; Wong, Xin Ai; Xiang, Mina; Xiao, Han Xin (International Journal of Tourism and Hospitality in Asia Pasific, 2024)
Shopee is one of the top-notch companies in the e-commerce field. It recorded 343 million visitors per month and its gross merchandise value was even aggregated to USD 19 billion in the second quarter of 2022. Shopee also expanded its business operations aggressively to new regions, namely Europe, Latin America, and South Korea. This study intends to examine the variables that influence customers’ online shopping behaviour in Shopee. A survey questionnaire is conducted to collect data from 150 Shopee’s users in Malaysia. The findings depicted that perceived trust and security, perceived service quality and perceived ease of use had influenced the customers’ online shopping behaviour towards Shopee in Malaysia. Perceived usefulness and perceived convenience did not greatly impact the customers’ online buying intention on Shopee in Malaysia. This study can provide Shopee with useful business insights about customers’ online shopping behaviour. It is recommended for Shopee Malaysia to prioritize the enhancement of three variables that exhibit a favorable correlation with customers' online shopping behavior, thereby ensuring business growth and expansion.